Spatial transparency in architecture : light, layering, and porosity - Rosales, Camilo (New York : Routledge, 2022)
"This volume explores the concept of 'spatial transparency'; a form of spatial continuity that articulates depth through permeable, layered or porous three-dimensional organizations where interstitial light is present. Although transparency is a concept largely associated with the modern movement, the use of glazed components, and twentieth century architectural discourse, spatial transparency is a form of depth awareness through intermediate domains, takes place through the interstitial fabric of a structure and occurs when several consecutive domains are spatially and visually connected. These immersive environments invite active participation, not as one-way communication but as a series of visual and experiential exchanges, interdependencies, and relationships. Divided into four parts, the book examines spatial transparency in massive opaque constructions, light constructions, glass assemblies and hybrid systems. It analyzes both the phenomenon of visual connectivity and continuity through intermediate spaces, and spatial transparency's capacity for promoting and enabling graded, interflowing environmental transactions. Using historical and contemporary examples, it catalogs some of the most common and recurring configurations that manifest these characteristics. Over 20 international case studies from the Americas to Japan are presented to argue that environments exist in porous mediums and that by studying the openings, voids, light, and materials of layered and/or permeable organizations, important insights about space making can be revealed. Written for students and academics, this book explores various expressions of spatial transparency in architecture and helps connect their abstract ideas with significant built works, analytical drawings and comparison charts"--
Keywords: Space (Architecture); Transparency in architecture; ARCHITECTURE / General; ARCHITECTURE / Design & Drafting; ARCHITECTURE / Methods & Materials